Multifluid and Kinetic 2D and 3D Simulations of Thermal Farley–Buneman Instability Turbulence in the Solar Chromosphere - Samuel Evans; Meers Oppenheim; Juan Martínez-Sykora; Yakov Dimant (The Astrophysical Journal)
Models currently fail to reproduce observations of the coldest regions in the Sun’s atmosphere, though recent work suggests the thermal Farley–Buneman instability (TFBI) may play a critical role. This meter-scale, electrostatic, multifluid plasma instability causes turbulence and heating in the coldest regions of the solar chromosphere. This paper describes how TFBI turbulence and heating varies across multifluid 2D, kinetic 2D, and kinetic 3D simulations. It also presents the first 3D simulations of the TFBI. We find that multifluid and kinetic 2D simulations produce similar results overall, despite using vastly different approaches. Additionally, our kinetic 3D simulations produce a similar or somewhat larger amount of heating compared to 2D, as contributions from the parallel electric field account for only (13 ± 2.5)% of the total turbulent heating in 3D.